2013
DOI: 10.1182/blood-2012-06-437160
|View full text |Cite
|
Sign up to set email alerts
|

Myelopoiesis is regulated by osteocytes through Gsα-dependent signaling

Abstract: Key Points• Deletion of Gs␣ in osteocytes induces severe osteopenia and a dramatic expansion of cells of the myeloid lineage.• Osteocytes regulate hematopoiesis and specifically contribute to myelopoiesis by secreting proliferative factors such as G-CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 32 publications
8
179
0
2
Order By: Relevance
“…Fulzele et al found that osteocytes participate in the regulation of myelopoiesis through the secretion of hematopoietic cytokines, such as G-CSF. They showed that the deletion of Gsa specifically in osteocytes greatly enhances G-CSF production, leading to the expansion of myeloid-committed cells, but not HSCs, in the BM [12].…”
Section: Osteocyte and Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Fulzele et al found that osteocytes participate in the regulation of myelopoiesis through the secretion of hematopoietic cytokines, such as G-CSF. They showed that the deletion of Gsa specifically in osteocytes greatly enhances G-CSF production, leading to the expansion of myeloid-committed cells, but not HSCs, in the BM [12].…”
Section: Osteocyte and Hematopoiesismentioning
confidence: 99%
“…A number of important roles for osteocytes in bone biology, such as mechanosensation and mineral metabolism, have been identified in previous studies [11]. A series of recent studies, including one by our group, has revealed the importance of osteocytes in the regulation of hematopoiesis [12][13][14]. In this review, we provide an overview of advances in our knowledge of regulatory mechanisms in the hematopoietic system by osteolineage cells in the endosteal area.…”
Section: Introductionmentioning
confidence: 99%
“…Ocy454 cells show rapid, high level expression of SOST/sclerostin that is responsive to hormonal (PTH), cytokine (PGE 2 ), and mechanical stimuli. Furthermore, G s ␣ knockdown in Ocy454 led to significant increases in SOST expression matching known osteocyte in vivo regulation (35), demonstrating the broad utility of this new osteocytic cell line for studying SOST/sclerostin regulation as we have recently reported (36). Ocy454 also showed an enhanced osteocytic phenotype when cultured on a three-dimensional biomaterial by increasing FGF23 expression upon PTH stimulation, highlighting the importance of optimizing in vitro culture conditions for studying certain aspects of osteocyte biology.…”
mentioning
confidence: 99%
“…Several studies found that deletion or mutation of functional genes in these niche cells led to MPNs, myelodysplasia, or leukemia [12,[28][29][30][31][32]. These findings and accordingly raised concepts were proved by the clinical transplantation investigations, in which donor-derived hematologic malignancies after hematopoietic stem cell transplantation were diagnosed [33].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 70%